Does soil carbon content explain inter-site differences in ecosystem respiration across the permafrost region? - Parmentier, F. J. W.; Belelli Marchesini, L.; Wille, C.; Hugelius, G.; Siewert, M. B.; Aurela, M.; Boike, J.; Christensen, T. R.; Dolman, A. J.; Friborg, T.; Goeckede, M.; Hensgens, G.; et al. (2024)
The permafrost region holds vast amounts of carbon which, upon thaw, may be released to the atmosphere as CO2 through enhanced decomposition. While links between soil carbon content and respiration have been shown by, for example, numerous incubation studies, it remains challenging to establish similar relationships from in-situ data collected in the field – especially at the large landscape-scale of eddy covariance towers. Part of the reason is the high heterogeneity of Arctic landscapes, combined with frequently shifting footprint distributions, and general lack of detailed soil carbon data that make it difficult to separate the signal from the noise. In this study, therefore, we combine detailed surveys of soil carbon content with high resolution footprint analyses to explore whether inter-site differences in ecosystem respiration across ten different sites in the Arctic can be explained by soil carbon content. Soil carbon data at each site was collected across dominant landforms and analyzed with depth. At 5 sites, these data were further developed into high resolution soil carbon maps. At the remaining sites, spatially weighted estimates of soil carbon content were determined proportionally to dominant landforms. Net CO2 fluxes collected by the towers were processed according to the same pipeline and partitioned into GPP and ecosystem respiration. These fluxes were related to the amount of soil carbon in the active layer at dominant landforms through a spatially explicit footprint analysis. Our preliminary results suggest that active layer soil carbon storage is a major predictor of inter-site differences in ecosystem respiration. This study will further explore the robustness of this relationship and how it relates to differences in climate, growing season length and plant productivity.